The development of the Coptic perceptions of the Muslim conquest of Egypt - Asfour, Walid Mohamed (AUC Knowledge Fountain, 2012)
This thesis examines some of the early Coptic perceptions of the Muslim conquest of Egypt that were mentioned in The Chronicle of John of Nikiu, written in the seventh century. It also compares it with the narratives in History of the Patriarchs of the Coptic Church of Alexandria which was collected in the 10th century. This comparison is aiming at recognizing the factors that could be responsible for the development of the Coptic perceptions on the Muslim conquest over three centuries. The study also examines if these sources are the production of a religious institute, such as the Coptic Church, or the mere work of individuals.